APLIKASI MARKETPLACE HASIL TANGKAP NELAYAN KABUPATEN GOWA BERBASIS ANDROID - Nurma Fitria; Faisal 2 (AGENTS: Journal of Artificial Intelligence and Data Science, 2022)
Marketing that is done traditionally faces problems due to the COVID-19 situation, people do not directly shop for fresh fish at fish auctions. An application was made to facilitate transactions between consumers and fishermen based on these problems. The purpose of this study is to design an Android-based marketplace for fishermen's catches to make it easier for fishermen and consumers to conduct online buying and selling transactions. This study uses quantitative research by collecting data through interviews, questionnaires, and literature studies. The system design is done by using Data Flow Diagrams, Use Case Diagrams, Class Diagrams, Activity Diagrams, and Sequence Diagrams. The interface is built using Android Studio and Firebase as the database. While testing the system using the BlackBox testing method and beta testing. The results of this study indicate that the Android-based marketplace application for fishermen's catches in Gowa Regency can help and make it easier for fishermen and consumers to make online fish buying and selling transactions. With test results from questionnaires for fishermen of 95.3% and consumers of 84.6% who concluded that the application helps sales and is easy to use.